WOMEN EMPOWERMENT THROUGH PARTICIPATION IN SMALL RUMINANTS REARING OF PASHTUN AND BALOCH TRIBAL CULTURE OF BALOCHISTAN-PAKISTAN: WOMEN EMPOWERMENT THROUGH PARTICIPATION IN SMALL RUMINANTS REARING OF PASHTUN AND BALOCH TRIBAL CULTURE OF BALOCHISTAN-PAKISTAN - Shafiq, Muhammad; Khan, Dr. Jahangir; Azhar, Asma; Rafiq, Nosheen; Bareach, Sadia (Hanken, 2018)
The objective of the study is to investigate the women empowerment through small ruminants’ rearing activities pertaining to Pashtun and Baloch tribal culture of Balochistan. Random sampling technique was used to collect the data through five-point Likert scale through selfconstructed questionnaire. Hypotheses were tested using correlation and regression analysis. Results indicated that women participation may not be able to empowered them; causing difficulties to adjust themselves in a stern Pashtun and Baloch culture. The main stay of the common people in Balochistan is on the rearing of livestock especially small ruminants’. Every family member takes an active part in small ruminants’ rearing Women Empowerment through Participation in Small Ruminants rearing of Pashtun and Baloch Tribal Culture of Balochistan-Pakistan activities. Women role in livestock rearing activities is significant. They work dawn to dusk and perform every activity within the boundaries of house. However, their participation regarding the livestock husbandry does not pay off which they deserve. In Pashtun and Baloch communities’ women have to stay within the boundaries of home, hence, culturally and traditionally they are not permitted to go outside without the permission of male members (Nunnally, & Bernstein, 1994). As majority of inhabitants are engaged with livestock rearing activities, hence, their main focus is livestock rearing especially small ruminants’ production. The results indicated that women empowerment relating to socio-economic, political, cultural and psychological are not substantive with the hypotheses. Factors such as Extensive illiteracy, lack of basic education, training and experience remain serious obstacles in women’s empowerment in Pashtun areas of Balochistan.